Protection of the right to equal recognition before the law of persons with limited capacity in the Republic of Latvia - Voznarska, Olga (Riga Graduate School of Law, 2020)
By restricting the ability of a person to make choices, guardianship excludes the person from a number of personal, social, and community experiences and thus creates a form of arbitrary and unreasonable segregation. Having addressed some of the issues with current guardianship legislation and why substituted decision is especially unacceptable for individuals with psychosocial conditions, this master thesis refers to the Convention on the Rights of Persons with Disabilities for normative support, to argue that gap yawns wide between what the 21st century’s first human rights treaty promises on paper and the lived reality of persons with limited capabilities in the Republic of Latvia. Social barriers, ranging from laws and policies to attitude of society and a lack of adequate support, continue to prevent persons with mental heath problems from enjoying their fundamental rights on an equal basis with others. Therefore, states should modify their existing legal capacity laws to provide alternative methods to partial guardianship as a less restrictive forma of support.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Public law::Constitutional law; Human rights